PECULIARITIES OF FORMING VALUE ORIENTATIONS OF RURAL SCHOOLCHILDREN - T. V. Vasilieva (Вестник Кемеровского государственного университета, 2013)
Value orientations of rural schools’ senior students are considered in the paper. The results of the research conducted with M. Rokeach’s technique of studying value orientations are presented. The features school students’ value orientations structure induced by rural society are defined.